Effect of Heat Transfer on Solar Module Output Voltage - Teuku Mizan Sya’rani Denk; Ary Firnanda; Herdian Saputra; T. M. Azis Pandria; Cut Daili (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Solar panels are an increasingly popular technology for generating electricity from sunlight. However, the performance of solar modules can be affected by various environmental factors, including heat transfer.High heat transfer can lead to an increase in the temperature of the solar panel and ultimately reduce the output voltage and energy conversion efficiency. Heat from the sun absorbed by the solar module can increase the temperature of the module and reduce the output voltage. Efforts must be made to reduce thetemperature of the solar panel so that the performance of the solar panel remains optimal. This manuscriptinvestigates the effect of heat transfer on the output voltage of solar modules. Various studies have beencarried out to evaluate the effect of heat transfer on solar module performance, taking into account factors such as the thermal conductivity of the module material, cooling design and environmental conditions. Theinstallation of a heat sink is one of the efforts made to cool the solar module. The heat sink can dissipate an average of 8710.16 joules/second, reducing the average temperature of the solar module by 37.57°C and increasing the average output voltage of the solar module to 19.4 volts. The results of this research showthat the use of heatsink material is better for reducing the temperature of solar modules. The use of a heat sink with a large surface area further accelerates the heat transfer process in the solar module